Studentpreneurship Program for Improving the Independence of Madrasah Ibtidaiyah Students in Temanggung Regency - Ibda, Hamidulloh; Rokhma, Eka Mahargiani; Wijanarko, Andrian Gandi (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
Background of the research is the lack of student’s independent attitude for completing school assignments and on entrepreneurship. The studentpreneurship program aims to improve students' moods and autonomy and it has never been implemented in Madrasah Ibtidaiyah Nahdlotut Tholibin Malebo, Kandangan, Temanggung. This study aims to evaluate the implementation of studentpreneurship program towards the student’s independence. This action research was conducted on three cycles phase, there are planning, implementation, observation, and reflection. The results expose that the students' independence attitudes increase after the implementation of the studentpreneurship program. In the pre-action, the value of students' independent attitudes was 31,42%, cycle I increased by 35,86%, and cycle II amounted to 72,14% (it can’t reach the 75% success indicator in cycle II). Cycle III was implemented and scored 80,71%. The results of Cycle III exceeded the expected success indicators, so the action in that cycle was stopped. The findings of this study may contribute to the study of science, especially on independence attitude development and the implementation of studentpreneurship programs in educational institutions. This study suggests that teachers implement the studentpreneurship program as a form of the Merdeka Belajar curriculum and adjusted it in curriculum for developing the students' independence earlier.